Gamma-ray irradiation of rice straw lignocellulose in aqueous NaOH as pretreatment for enxymatic hydrolysis - Macalintal, Jeric V. (2010)
Cellulosic Ethanol is a bio-fuel produced from the non-edible parts of plants. By using non-edible parts of plants, cellulosic ethanol is a possible solution to the problem regarding existing bio-fuels technologies and their threat to food security. In order to produce cellulosic ethanol, lignocellulosic biomass from plants must first be converted into glucose and then fermented. An important step in converting the lignocelluloses into sugar is the pretreatment phase where the biomass is made amenable to the subsequent hydrolysis process by increasing the biomass surface area and decreasing its crystallinity. One type of pretreatment is the gamma-ray irradiation of lignocelluloses. This study investigates the Cobalt-60 gamma-ray irradiation of rice straw lignocellulose. From a total of eight (8) 150mg samples of milled rice straw, two (2) samples were taken and sprayed with 4% NaOH solution and irradiated at the Philippine Nuclear Research Institute Cobalt-60 Multi-purpose Irradiation Facility (MIF) at the radiation level of 50kGy. Another two (2) samples were irradiated at 50kGy without being treated with NaOH. Another two (2) samples were treated with 4% NaOH solution alone. The last two (2) samples were not treated with NaOH nor irradiated. Enzymatic hydrolysis at 50°C using Cellulase from Trichoderma Reesei is performed for 24 hours on all eight (8) samples in order to produce glucose. From a baseline glucose yield of 10.62%, it was found that the irradiation at 50kGy of rice straw enahances the glucose yield by 118.55%, while the soaking of rice straw at 4% NaOH solution enhances the glucose yield by 10.45%. Combining irradiation and NaOH pretreatment of rice straw lessens the glucose yield by 25.8%. In addition to this, energy audit of the MIF during pretreatment determines the embodied energy of the Irradiation pretreatment process for rice-straw based ethanol to be 0.62MJ/kg.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman.
Keywords: Rice -- Effects of radiation; Gamma rays